GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KINERJA PENDIDIK - Nursyam Nursyam (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
The aims of this reseach to describe the leadership style of the head school at SMP Negeri 2 Baebunta to determine the performance of teachers in at SMP Negeri 2 Baebunta, to know the internal factors that contribute to developing the performance of educators in SMP Negeri 2 Baebunta, and to understand external factors that contribute in developing the performance of educators at SMP Negeri 2 Baebunta. This research is qualitative research that uses a religious approach, pedagogic approach, and managerial approach. Data collected by observation, interview and documentation. Data analyzed using by data reduction, data display, triangulation and conclusion. The result shows that leadership style of the principal of SMP Negeri 2 Baebunta applies decocratic style but apply authoritarian leadership when it is needed. Performance of teachers in SMP Negeri 2 Baebunta are accordance with the expectation of the principal where planningof learning, implementation of learning and the implementation of assessment have been going well likewise with the result of teachers’ performance includes the assessment of UTS and the UAS values are well. Internal factors consist strength and weakness include facilities and infrastructure teachers, and leadership of principal. External factor consist of opportunities and challenges can be seen from government policies, information and communication technology, and cooperation between the school parties.